An Analysis of Popular Online Erectile Dysfunction Supplements. Issue 6 (26th April 2019) - Balasubramanian, Adithya; Thirumavalavan, Nannan; Srivatsav, Ashwin; Yu, Justin; Hotaling, James M.; Lipshultz, Larry I.; Pastuszak, Alexander W.
ABSTRACT: Introduction: Erectile dysfunction supplements (ED-Ss) are featured on online marketplaces like Amazon.com, with dedicated pages and claims that they naturally treat ED. However, their efficacy and safety are largely unknown, limiting the ability to counsel patients regarding their use. Aim: To evaluate the highest rated and most frequently reviewed ED-Ss on Amazon.com to facilitate patient counseling regarding marketing myths, ingredient profiles, and evidence for product efficacy and safety. Methods: The Amazon marketplace was queried using the key term "erectile dysfunction" with default search settings and ranking items based on relevance. The top 6 ED-S products identified on September 29, 2018, were reviewed based on price, ratings, reviews, manufacturer, and ingredients. Consumer reviews were categorized using subtopics within the International Index of Erectile Function (IIEF) questionnaire to better understand ED-S efficacy and then reanalyzed following filtration of untrustworthy comments using ReviewMeta.com, a proprietary Amazon review analysis software. Outcomes: Quantitative and qualitative evaluation of ED-S products sold on Amazon.com . Results: The top 6 ED-Ss had an average of 2, 121 ± 1, 282 reviews and a mean rating of 3.92 ± 0.42 stars. A total of 21 ingredients were identified in these ED-Ss. Ginseng, horny goat weed, L-arginine, and tongkat ali were the most popular ingredients included in the analyzed products. Our literature review identified 413 studies involving the 21 identified ingredients, of which 59 (16%) involved human subjects. Among these 69 human studies, only 12 (17%) investigated supplement ingredients individually and reported improvement in ED. Analysis of top-ranked customer reviews from the first 2 pages of reviews for each supplement revealed differences in IIEF scores before and after ReviewMeta.com filtration. After filtration, we observed a 77% decrease in reviews reporting improved erection strength, an 83% decrease in reviews reporting improved ability to maintain erection, a 90% decrease in reviews reporting increased sexual satisfaction, an 88% decrease in reviews reporting increased enjoyment with intercourse, and an 89% decrease in reviews reporting increased erection confidence. Strengths & Limitations: Study strengths include a novel approach to ascertaining consumers' perceptions and satisfaction with ED-Ss and practical summary information that clinicians can provide to patients. Limitations include selection bias, the small number of supplements analyzed, and the proprietary nature of the Amazon review analysis software. Conclusions: Our investigation revealed that human studies evaluating the efficacy of ED-S ingredients are limited and have yielded no definitive findings of the effects on ED. Patients considering ED-S use should receive appropriate counseling, given the prevalence of disingenuous reviews and the ready availability of Food and Drug Administration–approved drug therapies.